Uji Aktivitas Antibakteri Ekstrak n-Heksana, Etil Asetat dan Etanol Kulit Bawang Merah (Allium cepa L.) terhadap Pertumbuhan Bakteri Salmonella typhi ATCC 6539 - Ferdiansyah Hakim; Hikmah Fitriani; Amanah Amanah (Universitas Pahlawan Tuanku Tambusai, 2026)
Salmonella typhi is the causative agent of typhoid fever and remains a major public health problem in developing countries. Irrational use of antibiotics may lead to bacterial resistance, thus alternative herbal therapies are needed. Red onion peel (Allium cepa L.) contains secondary metabolites such as flavonoids, alkaloids, saponins, and tannins that potentially exhibit antibacterial activity. This study aimed to analyze the antibacterial activity of n-hexane, ethyl acetate, and ethanol extracts of red onion peel against the growth of Salmonella typhi ATCC 6539.This study was an in vitro laboratory experimental study using a post-test only control group design. The population consisted of Salmonella typhi ATCC 6539 bacteria, while the samples were pure bacterial cultures grown on Salmonella Shigella Agar (SSA). Samples were obtained using a simple random sampling technique. The study consisted of 14 groups, including positive control (0.1% chloramphenicol), negative control (10% DMSO), and treatment groups of n-hexane, ethyl acetate, and ethanol extracts at concentrations of 40%, 60%, 80%, and 100%. Data were collected using the well diffusion method by measuring inhibition zones with a caliper. Data analysis was performed using the Shapiro-Wilk test followed by One-Way ANOVA and Post Hoc Bonferroni test.Phytochemical screening showed that ethyl acetate and ethanol extracts contained flavonoids, alkaloids, saponins, and tannins, whereas the n-hexane extract only contained alkaloids and saponins. The 100% ethyl acetate extract produced the largest mean inhibition zone of 9.17 mm, while the 40% concentration produced the smallest mean inhibition zone of 6.53 mm. The 100% ethanol extract produced a mean inhibition zone of 8.58 mm, while the 40% concentration produced 6.77 mm. The n-hexane extract showed no inhibition zone at all concentrations. One-Way ANOVA analysis demonstrated significant differences among treatment groups (p<0.05).Ethyl acetate and ethanol extracts of red onion peel (Allium cepa L.) exhibited antibacterial activity against Salmonella typhi ATCC 6539 with moderate inhibitory strength, while the n-hexane extract showed no antibacterial activity. The 100% ethyl acetate extract was the most effective treatment in inhibiting bacterial growth.